Relative prices in the People's Republic of China: Rural taxation through public monopsony - Stone, Bruce (International Food Policy Research Institute, 1988)
The government of the People's Republic of China has used agricultural price policies and other instruments which influence or determine relative prices in agriculture since the early 1950s. As the 1950s progressed, it became clear that price issues were sufficiently complex that a centralized independent organization was required expressly to supervise the establishment of appropriate prices and their periodic adjustment. Consequently, in July 1957, the National Price Commission was established. Although its operational development was arrested during the Great Leap Forward (1958-59) and the subsequent period of economic and administrational upheaval, the Commission was reestablished in 1963.